2020
DOI: 10.3390/nu12103062
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Consumption by Adult Rats Exposed to Dexamethasone In Utero Changes the Phenotype of Intestinal Epithelial Cells and Exacerbates Intestinal Gluconeogenesis

Abstract: Fructose consumption by rodents modulates both hepatic and intestinal lipid metabolism and gluconeogenesis. We have previously demonstrated that in utero exposure to dexamethasone (DEX) interacts with fructose consumption during adult life to exacerbate hepatic steatosis in rats. The aim of this study was to clarify if adult rats born to DEX-treated mothers would display differences in intestinal gluconeogenesis after excessive fructose intake. To address this issue, female Wistar rats were treated with DEX du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Both Cyclin D1 and PCNA expression as well as the number of Ki-67 positive cells, were increased in the liver of rats exposed to DEX in utero and treated with fructose during adulthood. Of note, we previously demonstrated that the small intestine of DEX+fructose rats also shows a high proliferative epithelium, resembling the metabolic and morphological features of the neonatal jejunum phenotype [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both Cyclin D1 and PCNA expression as well as the number of Ki-67 positive cells, were increased in the liver of rats exposed to DEX in utero and treated with fructose during adulthood. Of note, we previously demonstrated that the small intestine of DEX+fructose rats also shows a high proliferative epithelium, resembling the metabolic and morphological features of the neonatal jejunum phenotype [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presentation of how soluble extracts from chia seed (Salvia hispanica L.) affect brush border membrane functionality, morphology and intestinal bacterial populations in vivo (Gallus gallus) [21]. The fructose consumption by adult rats exposed to dexamethasone in utero changes the phenotype of intestinal epithelial cells and exacerbates intestinal gluconeogenesis [22]. Alterations in the intestinal morphology, gut microbiota, and trace mineral status following intra-amniotic administration (Gallus gallus) of teff (Eragrostis tef) seed extracts [23].…”
mentioning
confidence: 99%